AB0523 TAKAYASU ARTERITIS AND SACROILIITIS: A CASE-CONTROL STUDY. (2nd June 2020) - Regola, F.; Bosio, G.; Franceschini, F.; Toniati, P.
Abstract : Background: A possible shared immunopathogenesis between Spondyloarthritis (SpA) and Takayasu Arteritis (TA) has been hypothesized and some clinical cases about SpA in TA patients have been reported (1). In clinical practice the diagnosis of sacroiliitis may be performed by X-ray, Computed Tomography (CT) or Magnetic Resonance Imaging (MRI). In particular, CT findings of sacroiliitis include contour irregularities, joint space alterations, joint erosion, subcondral bone changes (osteoporosis or sclerosis), enthesitis, ankylosis. Meanwhile, TA patients performe routinely FDG-PET/CT scans for monitoring disease activity. Objectives: This study aims to understand if there is an increased incidence of sacroiliitis in TA patients. Methods: We collected retrospectively imaging data from FDG-PET/CT scans of 28 TA patients and 28 controls, matched for sex and age. Controls were selected among patients performing FDG-PET/CT in our Nuclear Medicine Unit, excluding patients with bone tumors, bone metastasis and thyroid cancers. The majority of controls were affected by lymphoma in complete remission. An expert rheumatologist read the CT-scans of sacroiliac joints. Results: No patients or controls demonstrated FDG-uptake in sacroiliac joints. In the control group we detected sacroiliac sclerosis in two cases: one due to degenerative changes, one to sacroiliitis (1/28, 4%). In the TA group four patients presented CT alterations suggestive for sacroiliitis: one bilateral erosion, one bilateral sclerosis, two monolateral sclerosis (4/28, 14%). One of these patients complained an inflammatory back pain. Conclusion: In our cohort of TA patients we demonstrated an increased prevalence of sacroiliitis, diagnosed by CT scan. Only one patient reported an inflammatory back pain, while three patients had radiological signs of previous sacroiliitis. These findings highlight the importance of looking for spondyloarthropathy in TA patients even if asymptomatic. References: [1]Guzel Esen S, Joint Bone Spine, 2019 Disclosure of Interests: None declared